1995
DOI: 10.2343/geochemj.29.213
|View full text |Cite
|
Sign up to set email alerts
|

Tetrad effects and fine structures of REE abundance patterns of granitic and rhyolitic rocks: ICP-AES determinations of REE and Y in eight GSJ reference rocks.

Abstract: All fourteen REE and Y have been determined for eight GSJ reference rocks including granitic and rhyolitic samples by ICP-AES with a preconcentration method. The two rhyolites (JR-1 and JR-2) and one granite (JG-2) exhibit convex tetrad effects of the M-type even in their chondrite-normalized REE patterns. Their tetrad effects, however, are modified from ideal ones by some step-like variations in their abundances from Tm to Lu. Similar step-like irregularities are seen commonly in chondrite-normalized patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 40 publications
1
60
0
Order By: Relevance
“…Hence OGr is more important than LHr in the discussion of tetrad effects in REE pat terns for geochemical samples (Kawabe, 1995;Kawabe et al, 1998). Since OGr = AHr T OSr, the tetrad effect in iHr is not exactly the same as that in AGr unless ASr is totally free from the tet rad effect (Kawabe, 1995). Attention should also be paid to a possible tetrad effect in AS,.…”
Section: Spectroscopic Studies Of Various Ln(iii) Commentioning
confidence: 99%
See 1 more Smart Citation
“…Hence OGr is more important than LHr in the discussion of tetrad effects in REE pat terns for geochemical samples (Kawabe, 1995;Kawabe et al, 1998). Since OGr = AHr T OSr, the tetrad effect in iHr is not exactly the same as that in AGr unless ASr is totally free from the tet rad effect (Kawabe, 1995). Attention should also be paid to a possible tetrad effect in AS,.…”
Section: Spectroscopic Studies Of Various Ln(iii) Commentioning
confidence: 99%
“…Lanthanide tetrad effects are observed in REE patterns for various geochemical samples (Masuda and Ikeuchi, 1979;Masuda et al, 1987;Akagi et al, 1993;Kawabe, 1995;Bau, 1996;Kawabe et al, 1998). The refined spin-pairing energy theory (RSPET) by Jorgensen (1979) is a theoretical ba sis of lanthanide tetrad effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the weathering cannot be used to explain the genesis of the REE tetrad effects in the granites. At present most workers agree that the tetrad REE pattern of highly evolved granites might have resulted from the fluid/melt interaction under open-system conditions at a late stage of magmatic evolution [51][52][53]. The granites that crystallized from the melts have "M" type REE patterns, whereas co-existing interactive fluids (external fluids and post-magmatic unmixing fluids) show "W" type REE patterns.…”
Section: Tetrad Effect In Ree Pattern and Highly Evolved Granitesmentioning
confidence: 99%
“…Recently, Zhao et al [46] reported an alkaline syenite with composite M-and W-type REE patterns. Now the REE tetrad effect can be considered to be caused by [47]: (1) fractionated accessory minerals containing different REE contents at a late stage of magmatic evolution [48,49], (2) the weathering near the surface [45,50], (3) fluids-melts interaction in the open system [51][52][53], and (4) granites suffering alteration by exsolved fluids separated from magmas with fluids-melts immiscibility [54]. Rayleigh model-based calculation suggests that REE tetrad effect stemming from the fractionation of accessory minerals needs an unreasonable accessory mineral assemblage [52,55].…”
Section: Tetrad Effect In Ree Pattern and Highly Evolved Granitesmentioning
confidence: 99%
“…A range of samples showing the fine structure in their REE patterns includes seawater, groundwater, leucogranite, kimuraite, marine sediments, Okuro deposits, rhyolite and shale. Many of the samples occur being associated with water phase, and wa ter seems to be primarily important to the effect (Masuda and Ikeuchi, 1979;Masuda et al, 1987;Masuda and Akagi, 1989;Hidaka et al, 1992;Akagi et al, 1993;Liu et al, 1993;Kawabe, 1995Kawabe, , 1996.…”
Section: Introductionmentioning
confidence: 99%